A Rapid and Specific HPLC Method to Determine Chemical and Radiochemical Purity of [68Ga]Ga-DOTA-Pentixafor (PET) Tracer: Development and Validation - Migliari, Silvia; Sammartano, Antonino; Scarlattei, Maura; Baldari, Giorgio; Silva, Claudia; Ruffini, Livia (Current Radiopharmaceuticals, 2021)
Background: Due to its overexpression in a variety of tumor types, the chemokine receptor 4 (CXCR4) represents a highly relevant diagnostic and therapeutic target in nuclear oncology. Recently, [68Ga]Ga-DOTA-Pentixafor has emerged as an excellent imaging agent for positron emission tomography (PET) of CXCR4 expression in vivo. Preparation conditions may influence the quality and in vivo behaviour of this tracer and no standard procedure for the quality controls (QCs) is available. Objective: The developed analytical test method was validated because a specific monograph in the Pharmacopoeia is not available for [68Ga]Ga-DOTA-Pentixafor. Method: A stepwise approach was used based on the quality by design (QbD) concept of the ICH Q2 (R1) and Q8 (Pharmaceutical Development) guidelines in accordance with the regulations and requirements of EANM, SNM, IAEA and WHO. Results: The purity and quality of the radiopharmaceutical obtained according to the proposed method were found to be high enough to safely administrate it to patients. Excellent linearity was found between 0.5 and 4 μg/mL, with a correlation coefficient (r2) for calibration curves being equal to 0.999, the average coefficient of variation (CV%) < 2% and average bias% that did not deviate more than 5% for all concentrations. Conclusion: This study developed a new rapid and simple HPLC method of analysis for the routine QCs of [68Ga]Ga-DOTA-Pentixafor to guarantee the high quality of the finished product before release.
Keywords: CXCR4 expression